Low-cost microcontroller platform for studying lymphatic biomechanics in vitro - Kornuta, Jeffrey A. (2012)
The pumping innate to collecting lymphatic vessels routinely exposes the endothelium to oscillatory wall shear stress and other dynamic forces. However, studying the mechanical sensitivity of the lymphatic endothelium remains a difficult task due to limitations of commercial or custom systems to apply a variety of time-varying stresses in vitro. Current biomechanical in vitro testing devices are very expensive, limited in capability, or highly complex; rendering them largely inaccessible to the endothelial cell biology community. To address these short-comings, the authors propose a reliable, low-cost platform for augmenting the capabilities of commercially available pumps to produce a wide variety of flow rate waveforms. In particular, the Arduino Uno, a microcontroller development board, is used to provide open-loop control of a digital peristaltic pump using precisely-timed serial commands. In addition, the flexibility of this platform is further demonstrated through its support of a custom-built cell-straining device capable of producing oscillatory strains with varying amplitudes and frequencies. Hence, this microcontroller development board is shown to be an inexpensive, precise, and easy-to-use tool for supplementing in vitro assays to quantify the effects of biomechanical forces on lymphatic endothelial cells.